Are risk weights of banks in the Czech Republic procyclical? Evidence from wavelet analysis - Václav Brož; Lukáš Pfeifer (Journal of Central Banking Theory and Practice, 2021)
We analyze the cyclicality of risk weights of banks in the Czech Republic from 2008 to 2016. We differentiate between risk weights under the internal ratings-based and those under the standardized approach, consider the financial cycle, and employ wavelet coherence as a means of dynamic correlation analysis. Our results indicate that the risk weights of exposures under the internal ratings-based approach, including risk weights related to exposures secured by real estate collateral, are procyclical with respect to the financial cycle. We also show that the effect of changing asset quality on risk weights is present for the internal ratings-based approach, in line with our expectations based on regulatory standards. Our results can be employed for the purposes of decision-making on the activation of supervisory and macroprudential instruments, including the countercyclical capital buffer.
Keywords: C14; E32; G21; G28; K23; 330; financial cycle; financial stability; internal ratings-based approach; risk weight; Bankrisiko; Kreditrisiko; Konjunktur; Basler Akkord; Tschechien